2008
DOI: 10.5704/moj.0811.008
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Method for Reconstruction of Chronic Rupture of the Quadriceps Tendon after Total Knee Replacement

Abstract: We describe herein a modified technique for reconstruction of chronic rupture of the quadriceps tendon in a patient with bilateral total knee replacement and distal realignment of the patella. The surgery involved the application of a Dacron graft and the 'double eights' technique. The patient achieved satisfactory results after surgery and we believe that this technique of reconstruction offers advantages over other methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…As there is currently no standardized strategy available for the treatment of chronic QTRs, surgical algorithms are merely based on personal experience and case reports 6–13 . In 2015, Rehman and Kovacs described a case in which a chronic QTR was treated successfully by a combined hamstring autograft and Prolene® mesh augmentation and an injection of autologous platelet‐rich plasma (PRP) to enhance graft incorporation 32 .…”
Section: Discussionmentioning
confidence: 99%
“…As there is currently no standardized strategy available for the treatment of chronic QTRs, surgical algorithms are merely based on personal experience and case reports 6–13 . In 2015, Rehman and Kovacs described a case in which a chronic QTR was treated successfully by a combined hamstring autograft and Prolene® mesh augmentation and an injection of autologous platelet‐rich plasma (PRP) to enhance graft incorporation 32 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, different types of Dacron grafts (i.e., Dacron tape) have been described in the literature. Singh et al report a variation with a double-eight fashion augmentation with a 6 mm Dacron graft in complex ruptures of the quadriceps, once again recognizing the earlier post-operative mobilization [ 13 ]. Fernandez-Baillo et al described a primary suture repair augmented with Dacron tape, with excellent results at 1-year follow-up [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fernandez-Baillo et al 9 observed a good outcome with the use of Dacron (US Catheter and Instrument, Glen Falls, New York) to reinforce an end-toend suture in a patient with rupture of the quadriceps tendon. Singh et al 16 reported a patient who underwent TKA and a second surgical intervention for recurrent patellar dislocation and then had partial rupture of the quadriceps tendon. After failure of conservative management, the patient received a Dacron graft using a figure-of-8 technique with the knee in full extension.…”
Section: Discussionmentioning
confidence: 99%